Think village please, researchers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
'In the smaller localities, where there are less than 500 villagers, farmers apply too much fertiliser because excessive deliveries are made by the state', writes Solomon Tadesse, an extension team coordinator, (PO Box 517, Debre-Zeit) in...